Unconditional bases of de Branges spaces and interpolation problems corresponding to them - Volkova, M. G.; Gubreev, G. M. (Methods of Functional Analysis and Topology, 2011)
In this paper the unconditional bases of de Branges spaces are constructed from the values of reproducing kernels. Appropriate problems of interpolation by entire functions are also considered. The paper is a continuation of papers [2, 3].